2011
DOI: 10.1186/1476-511x-10-33
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acids and the risk of metabolic syndrome in ethnic Chinese adults in Taiwan

Abstract: BackgroundEvidence of predictive power of various fatty acids on the risk of metabolic syndrome was scanty. We evaluated the role of various fatty acids, including saturated fat, monounsaturated fat, transfat, n-6 fatty acid, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), for the risk of the metabolic syndrome in Taiwan.ResultsA nested case-control study based on 1000 cases of metabolic syndrome and 1:1 matched control subjects. For saturated fat, monounsaturated fat and transfat, the higher the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Of the 48 articles examined by full-text, an additional 21 articles were excluded for various reasons (e.g., studies without providing n -3 PUFAs composition, studies from prospective cohort, or intervention studies). Finally, 27 studies were eligible for the present study, including 13 studies form Europe [ 8 , 9 , 13 , 14 , 15 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], 10 studies from Asia [ 10 , 11 , 12 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ], three studies from North America [ 16 , 34 , 35 ], and one study from South America [ 36 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 48 articles examined by full-text, an additional 21 articles were excluded for various reasons (e.g., studies without providing n -3 PUFAs composition, studies from prospective cohort, or intervention studies). Finally, 27 studies were eligible for the present study, including 13 studies form Europe [ 8 , 9 , 13 , 14 , 15 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], 10 studies from Asia [ 10 , 11 , 12 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ], three studies from North America [ 16 , 34 , 35 ], and one study from South America [ 36 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two prospective cohort studies investigated the association of circulating fatty acids with MetS risk, and the results have suggested null [ 8 ] and inverse associations [ 9 ]. Meanwhile, Several cross-sectional and case-control studies have indicated that plasma/serum n -3 PUFAs was significantly higher in healthy subjects compared with patients with MetS [ 10 , 11 , 12 , 13 ], while some studies have suggested opposite and null associations [ 8 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in US and European populations showed that different FAs in the circulation may play different roles in the development of CVD and T2D . In some earlier cross‐sectional or case‐control studies from Chinese populations, the protective roles of polyunsaturated fatty acids (PUFAs) were replicated for the risks of MetS, T2D, and hypertension . Moreover, long‐chain n‐3 FAs and stearic acid were inversely associated with increased incident myocardial infarction in the Singapore Chinese Health Study, whereas arachidonic acid exhibited a positive association .…”
Section: Studies Of Metabolomics In Chinese Populationsmentioning
confidence: 99%
“…[79][80][81] In some earlier cross-sectional or case-control studies from Chinese populations, the protective roles of polyunsaturated fatty acids (PUFAs) were replicated for the risks of MetS, T2D, and hypertension. [34][35][36][37][38][39][40] Moreover, longchain n-3 FAs and stearic acid were inversely associated with increased incident myocardial infarction in the Singapore Chinese Health Study, whereas arachidonic acid exhibited a positive association. 41 In the Nutrition and Health of Aging Population in China (NHAPC) study, a total of 28 erythrocyte FAs was detected by GC and a serial analysis was conducted to evaluate the effects of different FAs on the risks of cardiometabolic diseases.…”
Section: Application Of Metabolomics To Disease-related Risksmentioning
confidence: 99%
“…In this regard, trans-fatty acids and Omega-3 fatty acids (such as eiscosa pentaenoic acid) have been emphasized as risk factor and protective compound for CVD, respectively (8). Recent studies have shown that epicardial fat is a major risk factor for heart disease (9). The secretion of inflammatory cytokines from this adipose tissue and its proximity with coronary arteries one hand, and the role of epicardial fat in developing the risk factors for CVD including blood pressure on the other, may explain the role of epicardial fat in coronary artery disease (10).…”
Section: Introductionmentioning
confidence: 99%